Ambient-air-solution-processed efficient and highly stable perovskite solar cells based on CH3NH3PbI3−xClx-NiO composite with Al2O3/NiO interfacial engineering. (October 2017) - Wang, Yousheng; Mahmoudi, Tahmineh; Rho, Won-Yeop; Yang, Hwa-Young; Seo, Seunghui; Bhat, Kiesar Sideeq; Ahmad, Rafiq; Hahn, Yoon-Bong
Abstract: The poor air-stability and reproducibility of perovskite solar cells (PSCs) have prevented the practical applications of the devices that can withstand sustained operation under ambient air conditions. Here, we report all-ambient-air-solution-processed PSCs based on CH3 NH3 PbI3−x Clx -NiO composite film with inserting Al2 O3 /NiO at the TiO2 /perovskite interface in a cell configuration of FTO/c-TiO2 /mp-TiO2 /Al2 O3 /NiO/MAPbI3−x Clx -NiO/spiroOMeTAD/Au. The interface engineering with Al2 O3 /NiO not only improves crystalline quality of perovskite films and enhances charge transport, but also effectively suppresses carrier recombination. This composite-based interface engineering PSCs showed a high power conversion efficiency ( PCE ) of 18.14% and excellent reproducibility with average 16–18% PCE for 35 devices. More importantly, the devices without encapsulation showed a significant enhancement in long-term air-stability; the device photovoltaic parameters stabilized after 20 days and sustained its stability over 210 days with retaining ~100% of its original V oc, ~94% of J sc, ~91% of FF and ~86% of PCE in an ambient environment. Graphical abstract: SEM image and long-term air stability of ambient-air-solution-processed PSCs based on CH3 NH3 PbI3−x Clx -NiO composites with Al2 O3 /NiO interface engineering with FTO/c-TiO2 /mp-TiO2 /Al2 O3 /NiO/ MAPbI3−x Clx -NiO/Spiro-OMeTAD/Au configuration. Highlights: Ambient-air-solution-processed perovskite solar cells based on CH3 NH3 PbI3−x Clx –NiO with Al2 O3 /NiO interface engineering. High quality and excellent crystallinity of MAPbI3−x Clx –NiO composite film achieved by Al2 O3 /NiO interfacial engineering. High power conversion efficiency of 18.14%, small hysteresis and excellent reproducibility. Remarkable air-stability over 210 days with retaining ~100% of original Voc, ~94% of Jsc, ~91% of FF and ~86% of PCE .